Routes to failure and prevention recommendations in work systems of hydropower construction - Zheng, Xiazhong; Zhou, Jianlan; Wang, Fei; Chen, Yang (Journal of Civil Engineering and Management, 2018)
There are many types of accidents with their own characteristics in hydropower construction. The accidents are mainly results of human errors. It is important to find out the routes to failure and give recommendations pertinently for different accident types. First, 869 accident investigation reports are collected and the human factors are filtered using the Human Factors Analysis and Classification System (HFACS) framework, the norms which link the accident causes and human factors are also explored, the first three accident types are determined by the frequency statistics. The ranking of the factors and the norms of the three accident types is presented using the frequency statistics. The Chi-square, lambda and odds ratios are used to analyze the interdependences between adjacent level factors of three highest frequency accident types. At last, based on the correlation analysis between different human factors, the routes to failure can be determined; containing the norm frequency of factors, the safety recommendations are given to the different accident types pertinently. The results can be auxiliary and effective information for safety managers to conduct scientific and pertinent safety managements.